2015
DOI: 10.1101/gad.258855.115
|View full text |Cite
|
Sign up to set email alerts
|

A genetic screen reveals Foxa3 and TNFR1 as key regulators of liver repopulation

Abstract: The fundamental question of which genes are most important in controlling liver regeneration remains unanswered. We employed a parallel screen to test the impact of 43 selected genes on liver repopulation in the Fah −/− mouse model of hereditary tyrosinemia. We discovered that the transcription factor Foxa3 was a strong promoter of liver regeneration, while tumor necrosis factor receptor 1 (TNFR1) was the most significant suppressor of repopulation among all of the genes tested. Our approach enabled the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 38 publications
0
37
0
1
Order By: Relevance
“…Nodules of FAH‐positive hepatocytes were found in the livers, consistent with the clonal expansion of stably transduced hepatocytes seen with Sleeping Beauty –mediated gene therapy in Fah –/– mice (Fig. c, middle column) . MYC protein was strongly positive within the nuclei of hepatocytes in all three Fah –/– ; dCas9 + mice injected with TAlib1 but not in Fah –/– control mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nodules of FAH‐positive hepatocytes were found in the livers, consistent with the clonal expansion of stably transduced hepatocytes seen with Sleeping Beauty –mediated gene therapy in Fah –/– mice (Fig. c, middle column) . MYC protein was strongly positive within the nuclei of hepatocytes in all three Fah –/– ; dCas9 + mice injected with TAlib1 but not in Fah –/– control mice.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple independent gRNAs activated Myc expression to give a robust growth phenotype in a liver repopulation model. The phenotype is analogous to what we previously observed with Myc cDNA overexpression . Indeed, it was shown that liver‐directed Myc cDNA overexpression in transgenic animals resulted in hepatocellular carcinoma by 12‐15 months .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale was a previous study by Wangensteen et al demonstrating cMyc up‐regulation and Tnfrsf1a suppression after hepatocyte repopulation in FAH –/– mice. ( ) Further, multiple gRNAs per gene were used as this created a synergistic effect. ( ) In Lib2, the authors maintained gRNAs targeted toward cMyc, Tnfrsf1a, and control and introduced gRNAs specific for solute carrier family 7 member 11 (Slc7a11), another gene up‐regulated during repopulation in FAH –/– mice, and tumor protein P53 (Tp53), a tumor suppressor.…”
mentioning
confidence: 99%